Reclaiming Moral Nihilism - Veit, Walter (Revista de Filosofía, 2024)
Ever since John Leslie Mackie’s ‘popularization’ of moral error theories in meta-ethics, increasing attention has been focused on how to escape the force of nihilism. For many opponents of the moral error theory, ‘moral nihilism’ is used as a derogatory synonym associated with immorality and selfishness, but such a defamatory usage of the label is obviously not very helpful for a serious philosophical examination of the view. The goal of this paper is to draw on insights by David Hume and other Humean philosophers such as J.L. Mackie, Richard Joyce, and Richard Garner, in order to turn ‘moral nihilism’ from a term of abuse to a ‘badge of honour’.